THE EFFICIENCY OF UNIVERSITY RANKINGS: IMPLEMENTATION OF INFORMATIONAL AND MOTIVATIONAL FUNCTIONS - Liliya R. Yagudina; Iskander I. Yagudin (Высшее образование в России)
Basing on their hypothesis and an analysis of foreign studies, the authors determine how the information and motivational functions of rankings impact on Russian universities students' choice. The results of students' awareness of university rankings and student choices survey coincide with the global trends. The analysis of the ranking position of Russian universities and some of their key performance indicators (the foreign student number, the exam average score) showed that there is not any direct correlation between them. The authors believe that in order to maximize the effectiveness of rankings, it is necessary to improve the ranking methodology, to develop university decision making process based on the ranking results and to form the customer culture using the rankings results.